Terapia fotodinâmica e nanopartículas no controle de Xanthomonas campestris pv. campestris in vitro e em sementes de canola naturalmente contaminadas - Zancan, Nayara Lima Baute (2018)
Canola (Brassica napus) has been introduced in the Triângulo Mineiro and Alto Paranaíba in the recent years, but to keeping it up growing the seeds used must be free of pathogens. One of the most important bacterium disseminated through the canola seeds is Xanthomonas campestris pv. campestris (Xcc) causal agent of black rot in brassicas. Therefore, the objective of this work was to evaluate the efficacy of photodynamic therapy methods and the use of nanoparticles for the control of X. campestris pv. campestris in vitro and in the canola seed treatment. In the experiment of photodynamic therapy were used the photosensitive dyes, Methylene Blue, Toluidine Blue and the combination of both in different concentrations in vitro and in the seed treatment. In the second experiment were used different nanoparticles and its concentrations to the control of Xcc in vitro and in the seed treatment. Germination percentage, emergence rate, emergence speed index, sanity test and detection of the bacterium in the seeds were evaluated. Methylene Blue, Toluidine Blue and their association at concentrations 100, 50 and 25 μmol L-1 respectively, under irradiation were effectives to the Xcc control in vitro. The nanocrystals from ZnO doped with Ag, Au, Cu, Fe, Mn and Ni inhibited the bacterial growth in vitro using different concentrations, however, the nanocrystal ZnO:11Ag showed the larger bacterial inhibition halo. Therefore, it was not possible to estimate the effectiveness of the dyes and nanoparticles in the control of the bacteria in the seeds due to the low infection rate. Thus, new assays should be conducted to evaluate the concentration of dyes and nanoparticles in the control of the bacteria in seeds mainly because it presented toxicity to the canola seeds.